Pembuatan Pupuk Organik Cair Berbahan Dasar Limbah Batang Tembakau Secara Fermentasi Anaerob - Yasmiati; Nadya Lenvylea Laras; Ketut Sumada (Jurnal Serambi Engineering, 2025)
Tobacco is a widely cultivated agricultural commodity in Indonesia, producing significant waste in the form of stalks and roots. Currently, these wastes have not been widely utilized and are only dumped into the environment. Tobacco stalks contain essential nutrients and can potentially be used as raw material for liquid organic fertilizer (LOF). Therefore, research was conducted on the manufacture of liquid organic fertilizer from tobacco stem waste and evaluating the effect of tobacco stem weight and fermentation time on the quality of the LOF produced. The weights used were 25 g, 50 g, 75 g, 100 g, and 125 g, with fermentation times ranging from 1 to 5 weeks. The fermentation process was carried out in sealed bottles with additional coconut water, palm sugar, and EM-4, after cutting the stalks into small pieces (0.5–1 cm). The quality of the LOF was assessed based on organic carbon and nitrogen content using titrimetri and Kjeldahl methods. Results showed that increasing stalk weight elevated both organic carbon and nitrogen levels. Longer fermentation reduced organic carbon but increased nitrogen content up to an optimal point. Optimization of both variables is crucial to improve LOF quality.